Estudo espectroeletroquímico da hemeproteína extremófila HGbI (Hell's Gate Globin I) - Souza, Luiz Henrique da Costa (2020)
Among the globins identified in the microorganism Methylacidiphilum infernorum, a methanotroph that survives under extreme temperature and pH conditions, there is the Hell’s Gate Globin I (HGbI), a hemeprotein that present peculiar features, like stability in pH 2.8, pH-dependent hexacoordination in the reduced state (FeII), and an anomalous ability to coordinate acetate ion to the heme group. Despite the biological function of HGbI in the microorganism remains unsolved it is known there are interactions with the FeIII/II ion of the heme group which are dependent on the oxidation state. This work aimed the determination of the midpoint redox potential (Em) of the HGbI protein in the absence and presence of relevant molecules (cyanide, imidazole, carbo monoxide, acetate and oxygen) in solution of different pH values. For that, a spectroelectrochemical study was performed where the techniques electronic absorption spectroscopy in the ultraviolet and visible regions and electrolysis at controlled potential were coupled by using a thin layer spectroelectrochemical cell containing, besides the protein, different redox mediators. The determined Em values were as follows: 307, -330, - 501, -313 and -312 mV vs standard hydrogen electrode (SHE) in the absence and presence of imidazole, cyanide, oxygen and acetate, respectively. The measurements in medium containing CO showed hysteresis with oxidation and reductions potentials at 358 and -182 mV vs SHE, respectively. The catalytic assays in respect to the reduction reaction of acetate were monitored by UV-Vis in solutions of pH 5 and 8, with spectral changes being observed only in acid medium. The change in the spectral profile was assigned to the generation of a new compound resultant of acetate reduction. The spectroelectrochemical experiments in solutions of different pH values, besides allowed the determination of pKa (6.9; in the absence of ligand), provide support for suggesting lysine as the sixth ligand. The obtained results, in conjunction with the literature, reinforce the physiological function of HGbI is associated to the oxidation state of the iron atom and that it is not involved in the storage nor in the transport of oxygen in the Methylacidiphilum infernorum microorganism. Further studies are required for the confirmation of the sixth ligand as well as for the elucidation of the mechanism of the acetate reduction aiming to contribute for the understanding of the physiological function of HGbI.